An empirical research on exploring information sharing behaviour based on virtual teams. (12th May 2011) - Feng, Xiuzhen; Yue, Wenlei
Based on theory of reasoned action (TRA) and literature study regarding virtual teams, we conducted an empirical research on influential factors associated with information sharing behaviour of a virtual team and constructed a model for studying virtual team's information sharing behaviour. Taking advantage of an international course of BOHKNET as the sample of a virtual team, we tested various assumptions related to the model, verified the validity of the model, which confirmed these influential factors further grounded on analysing the data of collected questionnaires. Subsequently, we introduced some strategies for prompting information sharing of virtual teams.